2018
DOI: 10.1175/jhm-d-17-0155.1
|View full text |Cite
|
Sign up to set email alerts
|

Hydroclimatology of the Missouri River Basin

Abstract: Despite the importance of the Missouri River for navigation, recreation, habitat, hydroelectric power, and agriculture, relatively little is known about the basic hydroclimatology of the Missouri River basin (MRB). This is of particular concern given the droughts and floods that have occurred over the past several decades and the potential future exacerbation of these extremes by climate change. Here, observed and modeled hydroclimatic data and estimated natural flow records in the MRB are used to 1) assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 49 publications
4
74
0
Order By: Relevance
“…Lastly, the hydroclimatic analysis of the MRB presented in this paper serves as a complement to the hydroclimatic analysis of the Missouri River Basin (a major tributary of the MRB) presented by Wise et al. ().…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Lastly, the hydroclimatic analysis of the MRB presented in this paper serves as a complement to the hydroclimatic analysis of the Missouri River Basin (a major tributary of the MRB) presented by Wise et al. ().…”
Section: Discussionmentioning
confidence: 87%
“…Wise et al. () also reported that a long‐term negative trend (for years 1912 through 2011) in upper Missouri River Basin flows and a decrease in upper Missouri River snow vs. rain fractions (for years 1936 through 2011) were associated with warming spring temperatures. Wise et al.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations